INTERNALISASI NILAI – NILAI KARAKTER SEMANGAT DAN OPTIMISME SEBAGAI PENGUATAN IDENTITAS BUDAYA BANGSA PADA TARI GAMBYONG DI SANGGAR WAYANG GOGON TAHUN 2025 - Mayang Wijayanti; Siti Supeni; Sutoyo (STKIP Subang, 2026)
This study aims to describe and analyze the process of internalizing the character values of enthusiasm and optimism through Gambyong dance learning at Sanggar Wayang Gogon, identify the supporting and inhibiting factors, and formulate follow-up efforts for program development oriented toward improving artistic quality, career prospects, and the sustainability of the studio as a center of cultural education. The study employed a descriptive qualitative approach with an ethnographic strategy. The research subjects included the studio manager, dance instructors, and students participating in Gambyong dance learning. Data were collected through participant observation, in-depth interviews, and documentation study, and were analyzed through data reduction, data display, and conclusion drawing. Data validity was tested using source and technique triangulation. The findings show that the internalization of enthusiasm and optimism occurred through three stages: value transformation, value transaction, and transinternalization. Value transformation was carried out through the introduction of the philosophical meanings of Gambyong dance movements. Value transaction was evident in disciplined training habits, positive interactions between instructors and students, and the instructors’ role modeling. Transinternalization was reflected in students’ self-confidence, perseverance in practice, willingness to perform, and cheerful expressions during performances. Supporting factors included students’ motivation, a conducive studio environment, and opportunities to perform, while inhibiting factors included age differences, limited training time, and activities outside the studio. Mastery of character values increased by 25%–40% after regular training. Overall, Gambyong dance learning was effective in strengthening national cultural identity through cultivating enthusiasm and optimism in students’ daily behavior.